An homage to Peru’s bicentenary: Maxillaria bicentenaria (Orchidaceae), a new species previously misidentified as M. pyhalae - Martel, Carlos; Egoavil, Luis; Ocupa, Luis; Tello, Juan Andre; Rizo Patrón, Federico; Laura, César; León, Marco; Collantes, Benjamín (Phytotaxa, 2021)
We propose the new species Maxillaria bicentenaria from the montane forest of central Peru and provide an amendment of the description of Maxillaria pyhalae. Maxillaria bicentenaria is similar to M. pyhalae but differs by the elliptic to sub-elliptic labellum, the labellum distal half irregularly plicate, the flattened and transversally sub-trapezoidal labellar callus, the campanulate to sub-campanulate protuberance at the labellum apex centre, and the conspicuous carina with a sharp edge towards the top of the anther. Illustrations, pictures, and a distribution map are provided for both Maxillaria species. The differential features of both species are presented and previous misidentified records are discussed. Finally, a comment on the author name of Maxillaria fletcheriana is also provided.